Augen – Blick. Miniatur zu Robert Musil (Studia austriaca, 2016)
Objects are to some extent the result of them being viewed. Two eyes are the evident co-existence of aspects: they are able to see that which is not the point. The point, according to Hegel, would be something inexistent were it not for that relation to space of which it is the negation. Musil has described the way one looks at a point/spot, i.e. the way one actually does not do so – staring at something as if. The eyeballs are shivering: text might be the continous, faithfully making of changes, a shivering of the eyes of the text.